Dysregulation of the intrinsic apoptotic pathway mediates megakaryocytic hyperplasia in myeloproliferative neoplasms. Issue 11 (8th April 2016) - Malherbe, Jacques A J; Fuller, Kathryn A; Mirzai, Bob; Kavanagh, Simon; So, Chi-Chiu; Ip, Ho-Wan; Guo, Belinda B; Forsyth, Cecily; Howman, Rebecca; Erber, Wendy N
Abstract : Aims: Megakaryocyte expansion in myeloproliferative neoplasms (MPNs) is due to uncontrolled proliferation accompanied by dysregulation of proapoptotic and antiapoptotic mechanisms. Here we have investigated the intrinsic and extrinsic apoptotic pathways of megakaryocytes in human MPNs to further define the mechanisms involved. Methods: The megakaryocytic expression of proapoptotic caspase-8, caspase-9, Diablo, p53 and antiapoptotic survivin proteins was investigated in bone marrow specimens of the MPNs (n=145) and controls (n=15) using immunohistochemistry. The megakaryocyte percentage positivity was assessed by light microscopy and correlated with the MPN entity, JAK2 V617F / CALR mutation status and platelet count. Results: The proportion of megakaryocytes in the MPNs expressing caspase-8, caspase-9, Diablo, survivin and p53 was significantly greater than controls. A greater proportion of myeloproliferative megakaryocytes expressed survivin relative to its reciprocal inhibitor, Diablo. Differences were seen between myelofibrosis, polycythaemia vera and essential thrombocythaemia for caspase-9 and p53. CALR -mutated cases had greater megakaryocyte p53 positivity compared to those with the JAK2 V617F mutation. Proapoptotic caspase-9 expression showed a positive correlation with platelet count, which was most marked in myelofibrosis and CALR -mutated cases. Conclusions: Disruptions targeting the intrinsic apoptotic cascade promote megakaryocyte hyperplasia and thrombocytosis in the MPNs. There is progressive dysfunction of apoptosis as evidenced by the marked reduction in proapoptotic caspase-9 and accumulation of p53 in myelofibrosis. The dysfunction of caspase-9, which is necessary for proplatelet formation, may be the mechanism for the excess thrombocytosis associated with CALR mutations. Survivin seems to be the key protein mediating the megakaryocyte survival signature in the MPNs and is a potential therapeutic target.